Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions - GREGO, Jozef (European Journal of Taxonomy, 2020)
The genus Plagigeyeria Tomlin, 1930 is one of the most typical elements representing the stygobiont fauna in the southern Dinaric Alps. In the current study I present the territory of Hercegovina (and its adjacent regions of Bjelašnica and the Dalmatian coast containing transboundary aquifers) as one of the two main biodiversity hotspots for distribution of the genus. It is comparable with the species radiation of Plagigeyeria in the Kotor Bay–Skadar Lake Basin area. My study of the karst springs and caves revealed, besides the presently known species, twelve new Plagigeyeria taxa detected in so-far uninvestigated karstic aquifers: Plagigeyeria erossi sp. nov., P. ljutaensis sp. nov., P. konjicensis sp. nov., P. pseudocostellina sp. nov., P. reischuetzorum sp. nov., P. olsavskyi sp. nov., P. listicaensis sp. nov., P. ozimeci sp. nov., P. jakabi sp. nov., P. angyaldorkae sp. nov., P. vriosticaensis sp. nov. and P. lewarnei sp. nov. Closer shell morphology investigation supported by the protoconch morphology revealed a presence of another genus within the former Plagigeyeria complex. The following taxa are transferred herein to Travunijana Glöer & Grego, 2019: Plagigeyeria robusta Schütt, 1959, P. robusta asculpta Schütt, 1972, P. ovalis Kuščer, 1933, P. edlaueri Schütt, 1961, P. klemmi Schütt, 1961, P. nitida Schütt, 1963, P. angelovi Schütt, 1972 and P. tribunicae Schütt, 1963, plus a new species, Travunijana gloeri sp. nov., is described for the genus. Distribution maps of both genera, Plagigeyeria and Travunijana, over the karst aquifers of Hercegovina and adjacent regions are presented with respect to the hydrogeological separation of the known spring karst conduits and aquifers.